2008
DOI: 10.1002/anie.200804348
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Latent Fingerprints through the Detection of Drugs and Metabolites

Abstract: Magnetic particles functionalised with anti-cotinine antibody have been used to image latent fingermarks through the detection of the cotinine antigen in the sweat deposited within the fingerprints of smokers. The antibody–magnetic particle conjugates are readily applied to latent fingerprints while excess reagents are removed through the use of a magnetic wand. The results have shown that drug metabolites, such as cotinine, can be detected and used to image the fingermark to establish the identity of an indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
115
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(118 citation statements)
references
References 25 publications
0
115
0
1
Order By: Relevance
“…Hazarika et al have shown that drug metabolites such as benzoylecgonine, a major metabolite of cocaine, were present at a detectable level in the fingermarks of cocaine users [18,19]. In addition, the use of SALDI-TOF-MS enabled the detection of EDDP, a major metabolite of methadone, together with its parent drug in the same fingermark from an individual taking methadone [16].…”
Section: Application Of the Ceia For The Analysis Of Latent Fingermarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Hazarika et al have shown that drug metabolites such as benzoylecgonine, a major metabolite of cocaine, were present at a detectable level in the fingermarks of cocaine users [18,19]. In addition, the use of SALDI-TOF-MS enabled the detection of EDDP, a major metabolite of methadone, together with its parent drug in the same fingermark from an individual taking methadone [16].…”
Section: Application Of the Ceia For The Analysis Of Latent Fingermarksmentioning
confidence: 99%
“…However, recent advances by our research group using an immuno-labelling approach based on the use of fluorescently labelled, antibody-functionalised magnetic particles have shown the detection of drug metabolites endogenously produced in the latent fingermarks of drug users [18][19][20]. In addition, Rowell et al were able to show isolated patches of cocaine contamination in a fingerprint obtained from an individual being treated at a drug addiction centre using surface assisted laser desorption/ionisation time-of-flight mass spectrometry (SALDI-TOF-MS).…”
Section: Introductionmentioning
confidence: 99%
“…Characteristic compounds may be found in a latent fingerprint which could potentially be exploited to provide donor information such as age or a personal habit [4,5,31]. The individual amino acid and fatty acid composition data were studied to determine whether any quantitative variation arose as a consequence of a particular donor attribute, namely gender, diet, age and smoking.…”
Section: Individual Variation and Personal Traitsmentioning
confidence: 99%
“…A variety of strategies are employed in the development of new latent fingerprint enhancement techniques such as the exploitation of chemical analogues of existing reagents or the application of reagents used in other fields [2,3]. A further strategy involves the targeting of specific compounds in latent fingerprint residue, for example the detection of drug metabolites using antibodies immobilised on nanoparticles or the immunodetection of peptides and proteins [4,5,6]. In some instances these enhancement techniques may provide information about personal habits, as well as develop ridge detail [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation